2018
DOI: 10.1007/s00170-018-2495-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser powder bed fusion in high-pressure atmospheres

Abstract: High-speed imaging and schlieren imaging were used to investigate the interaction of the laser beam with the powder bed at pressures up to 5 bar, in argon and helium atmospheres. The entrainment of powder particles in the flow of shielding gas generated by the laser plume, and hence denudation, was reduced at high pressure for both gases. However, for argon, high pressure increased the temperature of both the melt pool and the laser plume, which significantly increased the generation of spatter and ionisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…Consequently, reporting the velocity threshold for both gases on figure 15, the entrainment width found in helium atmosphere is larger than that obtained in argon atmosphere, 3.3 against 2.5 times the laser spot radius respectively. Experimentally, this result is confirmed by Bidare et al [46]. They compared the widths of the denudation zones obtained in argon and helium atmospheres for different background pressures and different laser parameters and revealed that the denudation zone generated in helium where systematically larger than that generated in argon atmosphere.…”
Section: Application To Lpbf: Scaling Of Particle Entrainmentsupporting
confidence: 55%
“…Consequently, reporting the velocity threshold for both gases on figure 15, the entrainment width found in helium atmosphere is larger than that obtained in argon atmosphere, 3.3 against 2.5 times the laser spot radius respectively. Experimentally, this result is confirmed by Bidare et al [46]. They compared the widths of the denudation zones obtained in argon and helium atmospheres for different background pressures and different laser parameters and revealed that the denudation zone generated in helium where systematically larger than that generated in argon atmosphere.…”
Section: Application To Lpbf: Scaling Of Particle Entrainmentsupporting
confidence: 55%
“…This phenomenon was also pointed out experimentally by (Bidare, 2018) and suspected by (Mayi et al, 2019) using numerical simulation. During the keyhole formation and the vaporisation of the metal, a radial flow (of protective gas) directed toward the melt pool is induced Fig.…”
Section: Argon Versus Heliumsupporting
confidence: 64%
“…They also observed a faster contamination of the chamber with vapour fumes under helium. (Bidare et al, 2018) investigated the influence of gaseous atmosphere for pressures comprised between 1 and 5 bars. The use of helium was found to be beneficial at high pressure, with a more stable process, a constant amount of spatters and smoother bead surfaces with increasing power.…”
Section: Introductionmentioning
confidence: 99%
“…The metal vapor, which is expanding in all directions, transports adjacent powder particles away from the melt pool, so that they cannot contribute to the formation of the melt pool. Consequently, studies investigating LPBF with process pressure in the molecular flow regime [5-7, 9-11, 14] found increased powder spattering [8,14,16], but no clear evidence for any LPBF process improvements. A process pressure in the continuum flow regime and below atmospheric pressure has been investigated much less.…”
Section: State Of the Artmentioning
confidence: 99%